Drawing Lessons from Dissolution of Czechoslovakia in Addressing Possible Brexit Implications - Blanka Holigova (European Scientific Journal, ESJ, 2017)
It may appear there are hardly two other states that could be more different from each other than it is in the case of Czechoslovakia and the United Kingdom of Great Britain and Northern Ireland, however in hindsight of the latest development after the Brexit referendum and before triggering the notorious Article 50 of the Lisbon Treaty there could be some lessons drawn from the former development after the collapse of the Communist bloc setting into motion huge political changes in Europe from the perspective of dissolution of Czechoslovakia.